2023
DOI: 10.18632/aging.204475
|View full text |Cite
|
Sign up to set email alerts
|

Mitoquinone shifts energy metabolism to reduce ROS-induced oxeiptosis in female granulosa cells and mouse oocytes

Abstract: The female reproductive system is quite sensitive to regulation, and external environmental stimuli may cause oxidative stress which in turn may lead to accelerated aging and programmed cell death in female reproductive cells. The aim of this study was to investigate whether or not mitoquinone (MitoQ) could resist ROS-induced apoptosis in human granulosa cells and mouse oocytes. We found that the MitoQ treatment significantly reduced production of reactive oxygen species (ROS) and imbalance in mitochondrial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…However, high levels of oxidative stress induce PGAM5 release and translocation into the mitochondria, where it dephosphorylates AIFM1, the main effector of oxeiptosis. PDc was shown to decrease Keap1 accumulation, which is in contrast with what was described by Kang et al ( Kang et al, 2022 ), but in line with what was reported in Holze et al and Li et al works, in which higher levels of ROS oxidise Keap1 ( Holze et al, 2018 ; Tsui and Li, 2023 ). Moreover, recent work showed that Keap1 expression increases only in the first 2 h of ROS induction and then drops drastically ( Pallichankandy et al, 2023 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, high levels of oxidative stress induce PGAM5 release and translocation into the mitochondria, where it dephosphorylates AIFM1, the main effector of oxeiptosis. PDc was shown to decrease Keap1 accumulation, which is in contrast with what was described by Kang et al ( Kang et al, 2022 ), but in line with what was reported in Holze et al and Li et al works, in which higher levels of ROS oxidise Keap1 ( Holze et al, 2018 ; Tsui and Li, 2023 ). Moreover, recent work showed that Keap1 expression increases only in the first 2 h of ROS induction and then drops drastically ( Pallichankandy et al, 2023 ).…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that PGAM5 cleavage increases in conditions of stress, triggering different types of cell death ( Cheng et al, 2021 ). To corroborate this thesis, Li et al observed an increased cleavage of PGAM5 in conditions of high levels of ROS that induced oxeiptosis ( Tsui and Li, 2023 ). Interestingly, PGAM5 cleavage happens when it is located into the internal mitochondrial membrane ( Sekine et al, 2012 ), which is where AIFM1 is located.…”
Section: Discussionmentioning
confidence: 79%
“…Reactive oxygen species (ROS) is a critical factor for the maturation of germ cells. ROS is an active oxygen molecule that can be produced and removed in a living body through synthesis, decomposition, and operation (19). However, excessive reactive oxygen can damage germ cells and affect their maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondria are an important site of ROS production (66), and decline of mitochondrial quality during starvation (61,63,67) correlates with oxidative stress phenotypes of starved worms. To determine if the mitochondria are a source of the increased ROS levels observed in starved efk-1 mutants, we examined whether the starvation defect of the efk-1 mutant was altered by the mitochondrially targeted antioxidant mitoquinone (MitoQ) (68,69), which ameliorates stress-induced mitochondrial ROS generation and protects against mitochondrial dysfunction-induced phenotypes in mammalian cells and C. elegans (69)(70)(71). Indeed, MitoQ supplementation partially rescued the starvation survival defect of efk-1 mutants (Figure 7H; Figure S7I).…”
Section: Efk-1 Protects Against Mitochondrial Rosmentioning
confidence: 99%